Urogynecology: Evidence-Based Clinical Practice - Moore, Kate H. (Springer London : Imprint: Springer, 2013)
Urogynecology: Evidence Based Clinical Practice 2nd Edition is a fully revised and updated text providing an evidence based approach to the treatment of urinary incontinence and prolapse. This updated version incorporates new evidence in the areas of continence procedures, prolapse management, mesh usage and complications; in addition to new insights into Sacral Nerve Stimulation for refractory detrusor overactivity. Written by a leading expert in the field, Urogynecology: Evidence Based Clinical Practice 2nd Edition is a handy how-to guide, valuable for the junior registrar assigned to work in a urogynecology department, as well as for those with no previous formal urogynecological training who wish to know more about the subject.